IMPLEMENTASI METODE COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) BERBATUAN KOMIK PADA PEMBELAJARAN BAHASA INDONESIA KELAS IV DI SD NEGERI PAJURANGAN - Farihah Zamili; Didit Yulian Kasdriyanto; Faridahtul Jannah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Teachers who are less innovative in learning methods have a big impact on students' understanding of the material that has been explained. What needs to be done is that teachers must prepare and determine various methods and media to achieve the expected learning objectives. This research aims to determine the planning, implementation and evaluation of the application of the Cooperative Integrated Reading and Composition (CIRC) method assisted by comics in class IV Indonesian language learning at Pajurangan State Elementary School and to find out how this CIRC method can help overcome problems for students in understanding new vocabulary material with the affix meng. This research uses a qualitative method which involves collecting data in the form of descriptions or explanations of a series of words that describe data findings found during research activities in the field. The data collection proses was carried out through observation, interviews whit class teacher, school principals, students, and documentation. Based on the results of research data, the planning process involves preparing teaching modules and learning media related to the CIRC method that will be applied. Regarding the implementation of the Cooperative Integrated Reading and Composition (CIRC) method assisted by comics in class IV Indonesian language learning at Pajurangan State Elementary School, it involves stages that are in accordance with the steps of the CIRC method. The evaluation shows that the application of the CIRC method can help students quickly understand the material in Indonesian language learning and also create fun learning.